Methodological Aspects of Creating the System of Indicators of Crisis Prevention as the Foundation for Stabilization of Agricultural Production Based on Ukrainian Experience - Wasilewski, Mirosław; Orlykovskyi, Mykola; Poprozman, Natalia; Zaburanna, Lesia (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2016)
The article deals with the methodological principles of determining the indicators of the economic development of agricultural production, which are based on the requirements of the EU Common Agricultural Policy and which will identify the possibility of crises both in agriculture and its sub-sectors, as well as the national economy as a whole. The system which is reacting to the crisis indicators and allows assessment of the stability of economic development of agricultural production was proposed. Analytical approaches to diagnosis prehistory development and identify indicators – reacting to the crisis indicators by analyzing and evaluating indexes of dynamics in periods of stability (relatively stable path of development) and the crisis (sharp kink economic dynamics) and graphically analytical method of determination. For sectors show synthetic indicators (agricultural production, the level of monetization of the economy, import-export ratio) that serve as functional criteria for identify in previous periods of force majeure or crisis as precursor’s crisis.